Clinical presentation, microbiological characteristics, and their implications for perioperative outcomes in xanthogranulomatous pyelonephritis: perspectives from a real-world multicenter practice - TANIDIR, YILÖREN (My University, 2023)
Xanthogranulomatous pyelonephritis (XGP) is an uncommon chronic granulomatous infection of renal parenchyma. XGP is often associated with long-term urinary tract obstruction due to stones and infection. We aimed to analyze the clinical, laboratory, and microbial culture profiles from bladder and kidney urine of patients who were diagnosed with XGP. Databases of patients with histopathological diagnosis of XGP from 10 centers across 5 countries were retrospectively reviewed between 2018 and 2022. Patients with incomplete medical records were excluded. A total of 365 patients were included. There were 228 (62.5%) women. The mean age was 45 ± 14.4 years. The most common comorbidity was chronic kidney disease (71%). Multiple stones were present in 34.5% of cases. Bladder urine culture results were positive in 53.2% of cases. Kidney urine culture was positive in 81.9% of patients. Sepsis and septic shock were present in 13.4% and 6.6% of patients, respectively. Three deaths were reported. Escherichia coli was the most common isolated pathogen in both urine (28.4%) and kidney cultures (42.4%), followed by Proteus mirabilis in bladder urine cultures (6.3%) and Klebsiella pneumoniae (7.6%) in kidney cultures. Extended-spectrum beta-lactamases producing bacteria were reported in 6% of the bladder urine cultures. On multivariable analysis, urosepsis, recurrent urinary tract infections, increased creatinine, and disease extension to perirenal and pararenal space were independent factors associated with positive bladder urine cultures. On multivariable analysis, only the presence of anemia was significantly more frequent in patients with positive kidney cultures. Our results can help urologists counsel XGP patients undergoing nephrectomy.
Keywords: xanthogranulomatous pyelonephritis; urine culture; microbiology; urinary pathogens; prognosis